Analysis On Ashācirah And Ibādhīyah On The Attributes Of God - et. al., Mustafa Kamal Amat Misra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The basis for the development of the debate on the attributes of Allah is tanzīh and taqdīs which sanctify Allah of His every desire to every new thing. The responsibility is borne by the ulama' so that Allah who is the Most Perfect (kamāl) will remain perfect in human thought and not be tainted with deficient attributes (nuqsān). This debate on the attributes of God is discussed in the flow of kalām from the birth of its own thoughts and beliefs as well as systematic methodologies to help strengthen those beliefs. Like the Ibādhīyah sect with the Ahl al-Sunnah wa al-Jama'ah, its familiarity is acknowledged by the scholars Muhammad ibn Abu Zuhrah and Mustafa Wentan. With a qualitative study using document analysis method, this study will analyze the comparison will be done to examine the similarities and differences found in the discussion for Ibādhīyah and Ashācirah scholars. The study seeks, the basic understanding of the nature between Ibādhīyah and Ashācirah is the same nature is qadīm as a zāt. In addition to the various terms, the methodology of the division of attributes by Ashācirah is more perfect and easy to understand the methodology introduced by Ibādhīyah.